Long-Term Outcomes Following Laparoscopic and Abdominal Supracervical Hysterectomies - Marit Lieng; Anne Birthe Lømo; Erik Qvigstad (Hindawi Limited, 2010)
Long-term outcomes, in terms of cervical stump symptoms and overall patient satisfaction, were studied in women both after abdominal (SAH) and laparosocopic (LSH) supracervical hysterectomies. Altogether, 134 women had SAH and 315 women LSH during 2004 and 2005 at our department. The response rate of this retrospective study was 79%. Persistent vaginal bleeding after the surgery was reported by 17% in the SAH group and 24% in the LSH group. Regular bleeding was reported by only 8% in both study groups, and the women rarely found the bleeding bothersome. The women reported a significant pain reduction after the surgery, but women having a hysterectomy because of pain and/or endometriosis should be informed about the possibility of persistent symptoms. The overall patient satisfaction after both procedures was high, but the patients should have proper preoperative information about the possibility of cervical stump symptoms after any supracervical hysterectomy.